Temporal changes in the fecal microbiome and blood metabolites of early neonatal calves - Kojima, Miyu; Liu, Hong; Takemoto, Satoshi; Suda, Yoshihito; Inoue, Ryo; Watanabe, Gen; Jin, Wanzhu; Nagaoka, Kentaro (Frontiers in Animal Science, 2022)
The initial colonization and early development of the intestinal microbiome are important stages in the growth of calves during pre-weaning. Here we investigated temporal changes in diversity and composition of the fecal microbiota focusing on the first two weeks after birth, with the aim of identifying intestinal bacteria and blood metabolites that are associated with calf diarrhea. In this study, ten calves were fed colostrum on day 0 after birth, whole milk from day 2 to day 5 days, and milk replacer from day 6. Six calves showed mild diarrhea in the second week (from day 8 to day 14). We observed dramatic changes in the development of the fecal microbiome from day 2 to day 14 and found several bacteria, such as Lactobacillus and Collinsella, changing significantly in abundance during the milk transition (from day 4 to day 10). In investigating whether there is an association between the microbiome and the milk transition, we found the relative abundance of hypotaurine and D-xylose to be significantly higher in whole milk from day 4-5 than in milk replacer. A comparison of four healthy calves and six diarrheal calves revealed that the diarrheal calves had a low level of Collinsella on day 10. Furthermore, we explored plasma metabolites statistically correlated with the change of fecal Collinsella and found a high level of dimethylglycine in healthy calves. Taken together, these findings suggest possible link a temporary change in the fecal microbiome during the milk transition with diarrhea in early neonatal calves.